1996
DOI: 10.1086/mre.11.3.42629158
|View full text |Cite
|
Sign up to set email alerts
|

Marine Reserves for Fisheries Management

Abstract: Conventional methods of regulating commercial fisheries restrict catch by limiting either the quantity or efficiency of fishing effort, or by putting direct limits on catch. These regulatory practices are neither feasible nor desirable for many fisheries, and have failed to conserve fishery stocks in other fisheries. Marine reserves may be an effective alternative management strategy for some fisheries. Here we develop a dynamic model of marine reserves applicable to inshore fisheries. In contrast to previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
187
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(201 citation statements)
references
References 13 publications
12
187
0
2
Order By: Relevance
“…Also biologists have underlined the trade-off between short term profits from fisheries versus possible long term gains from risk reduction of marine reserves (Dayton et al 2000). This is however explicitly studied in Holland and Brazee's (1996) dynamic bioeconomic analysis where the discount rate of those affected by a reserve implementation, and their minimum production requirements, are critical with regards to policy decisions on marine reserves. If society discounts the future to a large degree, possible gains from marine reserves a long time ahead will not pay for the loss in economic activity today.…”
Section: Discounting the Futurementioning
confidence: 99%
See 2 more Smart Citations
“…Also biologists have underlined the trade-off between short term profits from fisheries versus possible long term gains from risk reduction of marine reserves (Dayton et al 2000). This is however explicitly studied in Holland and Brazee's (1996) dynamic bioeconomic analysis where the discount rate of those affected by a reserve implementation, and their minimum production requirements, are critical with regards to policy decisions on marine reserves. If society discounts the future to a large degree, possible gains from marine reserves a long time ahead will not pay for the loss in economic activity today.…”
Section: Discounting the Futurementioning
confidence: 99%
“…In the analysis of marine reserves, many economists have pointed to this fact (Holland and Brazee, 1996), and also shown that perfectly applied private property management without reserves will better take care of both stocks and harvests, unless marine reserves are exceedingly large (Hannesson, 1998). It is clearly not fair to assume that in fisheries with a high degree of sophisticated management, the implementation of marine reserves will eradicate all other management except perhaps access (see references to limited-entry management and marine reserves below).…”
Section: Management Options Outside the Reservementioning
confidence: 99%
See 1 more Smart Citation
“…The political motivation behind the introduction of marine reserves has also mainly had this focus. Recently, however, economic studies of marine reserves have shifted focus towards taking into account the economics of the fisheries as well (Holland and Brazee, 1996;Hannesson, 1998;Sanchirico and Wilen, 1999and Smith and Wilen, 2004. Hence the possibility of using marine reserves as a fisheries management tool has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the various regimes concentrates on efficiency; that is, economic rent in the fishing area, and the degree of conservation measured as fish density in the reserve. The analysis is static, leaving issues of transitional dynamics, and discounting the future, as discussed by Holland and Brazee (1996), for future analysis.…”
Section: Introductionmentioning
confidence: 99%